Lean supply chain management and its effects in automotive industry [electronic resource] - Sajad Mehrabbegi, 1983- (2011)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2011